-4x-5=2x + 7
6x=-12
x=-2
2007-01-25 09:48:35
·
answer #1
·
answered by wesnaw1 5
·
0⤊
0⤋
First: eliminate the parenthesis > use distribution - multiply the outer terms and signs with the terms in the parenthesis....
2 - (4x) - (7) = 3 + 2(x) + 2(2)
2 - 4x - 7 = 3 + 2x + 4
*Combine "like" terms...
2 - 7 - 4x = 3 + 4 + 2x
- 5 - 4x = 7 + 2x
Sec: add "5" to both sides....
- 5 + 5 - 4x = 7 + 2x + 5
- 4x = 12 + 2x
Third: subtract "2x" from both sides...
- 4x - 2x = 12 + 2x - 2x
- 6x = 12
*Isolate "x" on one side > divide both terms by "-6"...
-6x/-6 = 12/-6
x = - 2
2007-01-25 09:25:00
·
answer #2
·
answered by ♪♥Annie♥♪ 6
·
0⤊
0⤋
2-4x-7=3+2x+4(remove the brackets)
-5-4x=7+2x
-5-7=2x+4x(collect the terms)
-12=6x
=12/6=x
-2=x
x=-2
2007-01-28 18:36:24
·
answer #3
·
answered by srirad 2
·
0⤊
0⤋
x=-2
2007-01-25 09:18:27
·
answer #4
·
answered by Shawn Sizzle 2
·
0⤊
0⤋
2-(4x+7)= 3+2(x+2)
2-4x-7=3+2x+4
-4x-5=2x+7
-5=6x+7
-12=6x
-12/6=x
x=-2
2007-01-25 09:52:40
·
answer #5
·
answered by Dani Jo W 1
·
0⤊
0⤋
2-(4x+7)=3+2(x+2)
2-4x-7=3+2x+4
-5=7+6x
-12=6x
-2=x
2007-01-25 09:28:12
·
answer #6
·
answered by Pam L 1
·
0⤊
0⤋
2-(4x+7)=3+2(x+2)
2-4x-7-=3+2x+4
-5-4x=7+2x
-12=6x
-2=x
2007-01-25 09:28:17
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋